The Significance of Type-I Interferons in the Pathogenesis and Therapy of Human Immunodeficiency Virus 1 Infection - Wang, Bowen; Kang, Wen; Zuo, Jiahui; Kang, Wenzhen; Sun, Yongtao (Frontiers in Immunology, 2017)
Type-Ⅰ interferons (IFN-Ⅰ) are a widely expressed family that could promote anti-virus immunity in the process of pathogens invasion. In a human immunodeficiency virus 1 (HIV-1) infected individual, the production of IFN-Ⅰ can be detected as early as the acute phase and will persist throughout the course of infection. However, sustained stimulation of immune system by IFN-Ⅰ also contributes greatly to host-mediated immunopathology and diseases progression. Although the protective effects of IFN-Ⅰ in the acute phase of HIV-1 infection has been observed, more studies recently focus on their detrimental role in the chronic stage. Inhibition of IFN-Ⅰ signaling may reverse HIV-1-induced immune hyperactivation and furthermore reduce HIV-1 reservoirs, which suggest this strategy may provide a potential way to enhance the therapeutic effect of antiretroviral therapy. Therefore, we review the role of IFN-Ⅰ in HIV-1 progression, their effects on different immunocytes, and therapeutic prospects targeting the IFN-Ⅰ system.